Confirmation of Mycobacterium tuberculosis culture results with Ziehl-Neelsen staining and MPT64 antigen test - Indrasari, Witri; Dermawan, Asep; Sufa, Hafizah Ilmi; Kurniati, Iis (School of Veterinary Medicine and Biomedical Sciences, IPB University, Bogor, Indonesia, 2025)
Background Culture of Mycobacterium tuberculosis (MTB) using egg-based solid media like Lowenstein Jensen (LJ) is the gold standard for tuberculosis diagnosis but requires extended incubation time. Rapid diagnostic tests, such as Ziehl-Neelsen (ZN) staining and the MPT64 antigen rapid test, are essential for early detection. Objective This study aimed to evaluate the effectiveness of ZN staining and the MPT64 rapid test in detecting MTB and Mycobacterium other than tuberculosis (MOTT) during different culture times. Methods Using a cross-sectional design, 110 culture-positive samples were analyzed from Hasan Sadikin Hospital Bandung over two months. Specimens were cultured on LJ media for eight weeks, with weekly observation of colony growth. ZN staining and MPT64 tests were performed on growing colonies. Results Less than four weeks culture, 61 samples (55.5%) were culture-negative, 45 (40.9%) were positive for MOTT, and the remainder were contaminated. In more than four weeks culture, 48 samples (43.6%) were positive for MTB, 45 samples (40.9%) were positive for MOTT, and 13 (11.8%) were culture-negative, and the remaining were contaminated. ZN-positive and MPT64-negative results indicated MOTT in less than four weeks culture, while ZN-positive and MPT64-positive results indicated MTB in more than four weeks culture. Conclusion While ZN staining was positive for both MTB and MOTT colonies, the MPT64 rapid antigen test was specific for MTB, supporting its use in confirming MTB detection alongside culture methods.